Influence of minoxidil on ischemic cutaneous flaps in rats - Bittencourt,Rogério de Castro (2005)
PURPOSE: To evaluate the influence of minoxidil, a well known vasodilator, on ischemic flap necrosis prevention in rats. METHODS: Ventral cutaneous flaps, measuring 8x4cm, were designed in 20 Wistar rats based on the right cranial epigastric artery. In the experiment group, 50 mg/kg/day of minoxidil sulfate was administered by orogastric tube and the same amount of saline solution was administered to the control group. Such procedure was initiated 24h before surgery and kept once a day through the 7th postoperative day. Microcirculation was evaluated with laser fluxometry 24h before surgical procedure, at immediate postoperative and at the 7th postoperative day. Flap necrosis area was evaluated by 2 methods: planimetry and weight/paper ratio. RESULTS: A significant flow increase in distal and medial extremity at M1 (medial point 1) (p=0,0484) was observed in the experiment group. There was significant difference in flap necrosis prevention in the experiment group (p=0,0433), although after necrosis took place there was no significant difference in necrosis size. (p=0,1051 and p=0,2799). CONCLUSION: Minoxidil sulfate is effective in avoiding necrosis in ischemic flaps, but after necrosis is present there is no difference in survival area between experimental and control groups.